2021
DOI: 10.1007/s13346-021-00983-w
|View full text |Cite|
|
Sign up to set email alerts
|

Segmented intravaginal ring for the combination delivery of hydroxychloroquine and anti-CCR5 siRNA nanoparticles as a potential strategy for preventing HIV infection

Abstract: Vaginal drug delivery has been shown to be a promising strategy for the prevention of sexually transmitted infections. Therapy delivered at the site of infection has many advantages including improved therapeutic efficacy, reduction in systemic toxicity, and reduced potential for development of drug resistance. We developed a “smart” combination intravaginal ring (IVR) that will (1) provide continuous release of hydroxychloroquine (HCQ) to induce T cell immune quiescence as the first-line of defense and (2) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Similarly, PVA/γ-carregeenan films laden with PLGA–PEG-PEI nanoparticles showed significant improvements over aqueous nanoparticle formulations . Embedding nanoparticles within a matrix can also enable a stimulus-responsive release of nanoparticle payloads, as was demonstrated in the pH-responsive prophylactic delivery of mucopenetrating solid lipid nanoparticles (SLNs) laden with siRNA to prevent HIV infection . The selection of matrix form also impacts the delivery of embedded nanoparticle payload.…”
Section: Mucosae and Nanoparticle Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, PVA/γ-carregeenan films laden with PLGA–PEG-PEI nanoparticles showed significant improvements over aqueous nanoparticle formulations . Embedding nanoparticles within a matrix can also enable a stimulus-responsive release of nanoparticle payloads, as was demonstrated in the pH-responsive prophylactic delivery of mucopenetrating solid lipid nanoparticles (SLNs) laden with siRNA to prevent HIV infection . The selection of matrix form also impacts the delivery of embedded nanoparticle payload.…”
Section: Mucosae and Nanoparticle Designmentioning
confidence: 99%
“…157 Embedding nanoparticles within a matrix can also enable a stimulus-responsive release of nanoparticle payloads, as was demonstrated in the pH-responsive prophylactic delivery of mucopenetrating solid lipid nanoparticles (SLNs) laden with siRNA to prevent HIV infection. 159 The selection of matrix form also impacts the delivery of embedded nanoparticle payload. A direct comparison of mucoadhesive gels and nanofibers, both laden with chitosan nanoparticles, demonstrated that, while gels possess superior mucoadhesive properties, fibers provided higher drug permeation through vaginal tissue.…”
Section: Mucosae and Nanoparticle Designmentioning
confidence: 99%